An Orphan Generation - Torres Oviedo, Jairo Miguel (Revista Historia de la Educación Latinoamericana, 2022)
On October 11, in my capacity as president of the State University System, I participated in the "XIII International Congress on the History of Latin American Education". XIII International Congress History of Latin American Education"; event organized by the Pedagogical and Technological University of Colombia in the conference of master Boaventura de Sousa Santos. One of the most important sociologists of our time; advisor to the truth commission, who spoke on "the decolonization of knowledge and reinvention of power in times of pandemic"; therefore, I will address one of the theses presented by Professor Boaventura about the weight of history, thus, contextualize it in the national reality. The weight of history is variable, there are periods in which history is heavy and in others light.